OVERVIEW OF THE USE OF LEARNING MEDIA USING BIBLIOMETRIC ANALYSIS - Eli Sabrifha (Kutubkhanah, 2022)
This study aims to provide an overview of the most relevant theme assessors related to Teachers use media in learning with bibliometric analysis using the keywords "Teachers use "OR" media in learning "OR" teachers use me" as input to obtain a full understanding of Teachers use media in learning and understand current research concentrations. Using the Scopus data source as it is considered the best choice for bibliometric analysis. The method used is literature review using bibliometric analysis to visualize the network of authors, quotes and keywords, VOSviewer software. The results show that Every year, there are more and more papers on Teachers use media in learning, a trend that shows increasing interest in the subject. Hecker, T is the author with the most citations and documents overall while Virginia is the university with the most published articles. The bibliometric analysis offers relevant details on the main issues studied about Teachers use media in learning.